INVESTOR ATTENTION TO ESG AND THE UNDERPERFORMANCE OF HIGH-ESG STOCKS - Bahadır, Oğuzhan; Akarsu, Sergen; Özdarak, Eylül (Economic Review: Journal of Economics and Business, 2025)
This paper examines how investor attention affects the relationship between environmental, social, and governance (ESG) scores and stock returns. ESG performance is measured using Refinitiv’s combined ESG scores, and return differences between high- and low-ESG portfolios are analyzed. Google Trends data are also used to assess the role of investor attention. It is found that low-ESG stocks exhibit higher return volatility and market beta, resulting in higher returns compared to high-ESG stocks. The performance gap between high- and low-ESG stocks becomes more pronounced following significant events such as the Global Financial Crisis and the COVID-19 pandemic. Increased investor attention to ESG further magnifies the underperformance of high-ESG firms. Additionally, it is demonstrated that the pandemic drew investor attention to ESG, contributing substantially to return differences. Specifically, the return difference between the highest- and lowest-ESG portfolios increases by 6.25 percentage points for every 1% increase in abnormal investor attention following the onset of the pandemic. This study contributes to the literature by emphasizing the role of investor attention in the relationship between ESG scores and stock returns.